PARTICIPATION OF FPU (FORMED POLICE UNIT) 8 INDONESIA IN UNAMID IN DARFUR, SUDAN PERIOD 2016-2017 - Darajat, Iklima Tami; Tatok Djoko Sudiarto (ZILLZELL MEDIA PRIMA, 2023)
This study aims to analyze the involvement of Indonesian FPU (8) at UNAMID in Darfur, Sudan Period 2016-2017. To analyze the case, the author uses several concepts such as, Ethnic Conflict, Preventive Diplomacy, Humanitarian Intervention and Peace Keeping. This research is a qualitative research. The results of this study show that in an effort to muffling a protracted conflict in Darfur-Sudan, caused by the Janjaweed militia and support from Sudanese government that resulted in Ethnic Genocide on Darfur, Sudan. Seen from the prolonged conflict in Darfur, PBB issued a joint Resolution in Darfur-Sudan, called UNAMID (United Nations-African Mission in Darfur). Indonesia as a country that maintain peace feels compelled to participate in peace and security missions in Darfur- Sudan. With the agreement between the United Nations and Indonesia, Indonesia sent the FPU Police Task Force to Darfur-Sudan as a Peace Operation to stop the conflict in Darfur, Sudan. In his duty FPU 8 Indonesia as PKO, has important duties: 1) Maintain Conflict in the form of ceasefire and humanitarian protection and, 2) Conserve peace in the form of human rights and humanitarian aid.